Single-cell multi-omics sequencing of human early embryos - Li, Lin; Guo, Fan; Gao, Yun; Ren, Yixin; Yuan, Peng; Yan, Liying; Li, Rong; Lian, Ying; Li, Jingyun; Hu, Boqiang; Gao, Junpeng; Wen, Lu; et al. (Nature cell biology, 2018)
DNA methylation, chromatin states and their interrelationships represent critical epigenetic information, but these are largely unknown in human early embryos. Here, we apply single-cell chromatin overall omic-scale landscape sequencing (scCOOL-seq) to generate a genome-wide map of DNA methylation and chromatin accessibility at single-cell resolution during human preimplantation development. Unlike in mice, the chromatin of the paternal genome is already more open than that of the maternal genome at the mid-zygote stage in humans, and this state is maintained until the 4-cell stage. After fertilization, genes with high variations in DNA methylation, and those with high variations in chromatin accessibility, tend to be two different sets. Furthermore, 1,797 out of 5,155 (35%) widely open chromatin regions in promoters closed when transcription activity was inhibited, indicating a feedback mechanism between transcription and open chromatin maintenance. Our work paves the way for dissecting the complex, yet highly coordinated, epigenetic reprogramming during human preimplantation development.